Design, synthesis and molecular docking of novel diarylcyclohexenone and diarylindazole derivatives as tubulin polymerization inhibitors - Riham I. Ahmed; Essam Eldin A. Osman; Fadi M. Awadallah; Samir M. El-Moghazy (Taylor & Francis Group, 2017)
New target compounds were designed as inhibitors of tubulin polymerization relying on using two types of ring B models (cyclohexenone and indazole) to replace the central ring in colchicine. Different functional groups (R1) were attached to manipulate their physicochemical properties and/or their biological activity. The designed compounds were assessed for their antitumor activity on HCT-116 and MCF-7 cancer cell lines. Compounds 4b, 5e and 5f exhibited comparable or higher potency than colchicine against colon HCT-116 and MCF-7 tumor cells. The mechanism of the antitumor activity was investigated through evaluating the tubulin inhibition potential of the active compounds. Compounds 4b, 5e and 5f showed percentage inhibition of tubulin in both cell line homogenates ranging from 79.72% to 89.31%. Cell cycle analysis of compounds 4b, 5e and 5f revealed cell cycle arrest at G2/M phase. Molecular docking revealed the binding mode of these new compounds into the colchicine binding site of tubulin.